Teacher Readiness in Integrating Technology in English Language Lessons - Lucille, Ngu (Universiti Malaysia Sarawak, 2024)
The Malaysian National Education Blueprint (2013) set forth a ten-year plan for English language education reform, emphasising a systematic approach to curriculum and the significant role of technology in improving teaching and learning. At the core of it, teachers as the agent of transformation are required to be equipped to effectively integrate technology in classroom instruction. This calls for teachers to develop the teacher knowledge necessary for the task – the Technological Pedagogical Content Knowledge (TPACK). This study investigated teacher readiness in integrating technology in English language lessons, by looking at their level of TPACK, and also the factors determining their TPACK. This study involved 201 in-service secondary school English language teachers in Sarawak, Malaysia. This mixed-method study utilised an adapted questionnaire by Baser et al. (2016) and an adapted interview protocol by Slutsky (2016). The findings showed that teachers have high Technological Knowledge, Pedagogical Knowledge, Technological Pedagogical Knowledge, Technological Content Knowledge, and Technological Pedagogical Content Knowledge, and very high Content Knowledge and Pedagogical Content Knowledge. Students, learning autonomy, professional support, institutional support, proven success, and curriculum were found to be factors determining teachers’ TPACK.